Multiple gastrointestinal stromal tumors in a young patient: a case report - Tobar Carmona, Javiera; Szwarcfiter Neiman, Vania (Revista Chilena de Estudiantes de Medicina, 2024)
Introduction: Gastrointestinal Stromal Tumors (GIST) are mesenchymal neoplasms originating from the interstitial cells of Cajal. They are rare tumors, mainly occurring in older adults and typically presenting as solitary masses. Diagnosis is confirmed through histopathology and immunohistochemistry (IHC). Mutational analysis is necessary as it carries therapeutic and prognostic implications. Case presentation: A 24-year-old woman presents with rapidly progressive fatigue, palpitations, orthostatic headache, and sleepiness. Physical examination reveals tachycardia, pallor, and slowed capillary refill. Initial studies show severe microcytic hypochromic anemia and marked iron deficiency. Upper gastrointestinal endoscopy reveals a gastric polyp and a subepithelial lesion. Scans show two gastric lesions and omental nodules. A biopsy of the polyp confirms gastric GIST. Surgical management is decided upon. Genetic testing is performed, ruling out the need for immunotherapy. Discussion: GISTs are rare mesenchymal neoplasms of the digestive tract, predominantly affecting older adults and usually presenting as solitary masses. The rarity of the case presented above is underscored by the atypical age of onset and the unusual presentation. In this context, mutational analysis becomes crucial to determine the need for long-term treatment and prognosis.